Belowground Phytolith-Occluded Carbon of Monopodial Bamboo in China: An Overlooked Carbon Stock - Chen, Chen; Huang, Zhangting; Jiang, Peikun; Chen, Junhui; Wu, Jiasen (Frontiers in Plant Science, 2018)
Phytolith-occluded carbon (PhytOC), a highly stable carbon (C) fraction resistant to decomposition, plays an important role in long-term global C sequestration. Previous studies have demonstrated that bamboo plants contribute greatly to PhytOC sink in forests based on their aboveground biomass. However, little is known about the contribution of belowground parts of bamboo to the PhytOC stock. Here, we reported the phytolith and PhytOC accumulation in belowground trunk and rhizome of eight monopodial bamboo species that widely distributed across China. The results showed that the belowground parts made up an average of 39.41% of the total plant biomass of the eight bamboo species. There were significant (p < 0.05) variations in the phytolith and PhytOC concentrations in the belowground trunk and rhizome between the bamboo species. The mean concentrations of PhytOC in dry biomass ranged from 0.34 to 0.83 g kg-1 in the belowground rhizome and from 0.10 to 0.94 g kg-1 in the belowground trunk across the eight bamboo species, respectively. The mean PhytOC stocks in belowground biomass ranged from 2.57 to 23.71 kg ha-1, occupying an average of 23.36% of the total plant PhytOC stocks. This implies that 1.01×105 t PhytOC was overlooked based on the distribution of monopodial bamboos across China. Therefore, our results suggest that the belowground biomass of bamboo represents an important PhytOC stock, and should be taken into account in future studies in order to better quantifying PhytOC sequestration capacity.